1988
DOI: 10.1099/00221287-134-7-1983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hexadecane-induced Vesiculation on the Outer Membrane of Acinetobacter calcoaceticus

Abstract: Lipopolysaccharide-rich vesicles were released from Acinetobacter calcoaceticus 69V during growth on hexadecane. Vesicle formation occurred over the whole surface of the cell as demonstrated by scanning electron microscopy. In contrast, the surface of acetate-grown cells, for which little lipopolysaccharide was found in the growth medium, appeared smooth. The overall chemical composition as well as the protein and phospholipid composition of the outer membranes of both cell types was very similar. In the vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For N. meningitidis it was shown that cysteine depletion causes oxidative stress which triggered OMV release [81]. Also a number of media components can induce OMV production such as hexadecane for Acinetobacter [83], glucose for Yersinia [32, 84] and sodium carbonate for V. cholerae [85]. In P. aeruginosa the signal molecule PQS promotes OMV release [59], or under anoxic conditions, when no PQS can be synthesized, the bactericidal toxin pyocin [86].…”
Section: Natural Omvmentioning
confidence: 99%
“…For N. meningitidis it was shown that cysteine depletion causes oxidative stress which triggered OMV release [81]. Also a number of media components can induce OMV production such as hexadecane for Acinetobacter [83], glucose for Yersinia [32, 84] and sodium carbonate for V. cholerae [85]. In P. aeruginosa the signal molecule PQS promotes OMV release [59], or under anoxic conditions, when no PQS can be synthesized, the bactericidal toxin pyocin [86].…”
Section: Natural Omvmentioning
confidence: 99%
“…The release of DNA-containing OMVs from pathogenic species of Acinetobacter has also been previously reported (25)(26)(27). Acinetobacter baylyi (previously also denoted Acinetobacter calcoaceticus) has been described to release OMVs when grown on hexadecane (28).…”
mentioning
confidence: 98%
“…5). Examples of this are the chaperones that assist in proper protein folding and functioning, and the intracellular trafficking, secretion and vesicular transport transcripts that are involved in production of outer membrane vesicles formation through blebbing (Toyofuku et al ., 2019) which can eject toxic agents when bacteria are grown on ADOC‐rich or other hydrophobic compound‐rich media (Borneleit et al ., 1988; Kobayashi et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%